Water‐Triggered Spontaneously Solidified Adhesive: From Instant and Strong Underwater Adhesion to In Situ Signal Transmission - Zheng, Si Yu; Zhou, Jiahui; Wang, Shuaibing; Wang, Yan‐Jie; Liu, Shanqiu; Du, Guangyan; Zhang, Dong; Fu, Jimin; Lin, Ji; Wu, Zi Liang; Zheng, Qiang; Yang, Jintao (Advanced functional materials, 2022)
Developing conductive underwater glue for fast sealing and in situ monitoring is critical for ocean exploration yet remains a challenge. The fluidity of glue is a double‐edged sword that is favorable for molecule spreading and formation of interlocking bonding network yet also leads to leakage of conductive ions. Herein, a polymeric glue possessing good conductivity and exhibiting rapid, strong, and long‐lasting underwater adhesion on diverse substrates at various harsh environments and extreme temperatures is developed. For molecular design, the nitrogen heterocyclic motif that prevails in biomolecular recognition is encoded with water‐resistant benzene block in one pendant group to serve as underwater binding sites; ionic liquids (ILs) of [EMIM][BF4] is employed as the solvent for fast water exchange that triggers rapid adhesion. Simultaneously, the polymer‐IL interaction is regulated, with the assistance of the theoretical calculations, to retain sufficient ILs within the adhesive for sensing. Finally, the glue is applied for underwater sealing and in situ monitoring various physical signals, while the fluorescent property is utilized for underwater labeling. This study should provide a new design strategy for the next‐generation of multifunctional underwater adhesives and promote their applications. S. Y. Zheng, J. Zhou, S. Wang, Y.‐J. Wang, S. Liu, G. Du, D. Zhang, J. Fu, J. Lin, Z. L. Wu, Q. Zheng, J. Yang A polymeric glue simultaneously exhibiting rapid, strong, and long‐lasting adhesion on diverse substrates against various harsh environments and extreme temperatures, along with functions of underwater sensing and fluorescent labeling is developed. The comprehensive adhesion efficiency of the adhesive outperforms most existing underwater adhesives and should provide a new strategy for the molecular design of the next‐generation underwater adhesives.